Feeding a diet contaminated with ochratoxin A for broiler chickens at the maximum level recommended by the EU for poultry feeds (0.1 mg/kg). 2. Effects on meat quality, oxidative stress, residues and histological traits. Issue 1 (2nd May 2013) - Pozzo, L.; Cavallarin, L.; Antoniazzi, S.; Guerre, P.; Biasibetti, E.; Capucchio, M. T.; Schiavone, A.
Summary: The European Commission Recommendation 2006/576/EC indicates that the maximum tolerable level of ochratoxin A (OTA) in poultry feeds is 0.1 mg OTA/kg. Thirty‐six 1‐day‐old male broiler chicks were divided into two groups, a control (basal diet) and an OTA (basal diet + 0.1 mg OTA/kg) group. The OTA concentration was quantified in serum, liver, kidney, breast and thigh samples. The thiobarbituric acid reactive substances (TBARS) content were evaluated in the liver, kidney, breast and thigh samples. The glutathione (GSH) content, and catalase (CAT) and superoxide dismutase (SOD) activity were measured in the liver and kidney samples. Histopathological traits were evaluated for the spleen, bursa of Fabricius and liver samples. Moreover, the chemical composition of the meat was analysed in breast and thigh samples. In the OTA diet‐fed animals, a serum OTA concentration of 1.15 ± 0.35 ng/ml was found, and OTA was also detected in kidney and liver at 3.58 ± 0.85 ng OTA/g f.w. and 1.92 ± 0.21 ng OTA/g f.w., respectively. The TBARS content was higher in the kidney of the ochratoxin A group (1.53 ± 0.18 nmol/mg protein vs. 0.91 ± 0.25 nmol/mg protein). Feeding OTA at 0.1 mg OTA/kg also resulted in degenerative lesions in the spleen, bursa of Fabricius and liver. The maximum tolerable level of 0.1 mg OTA/kg, established for poultry feeds by the EU, represents a safe limit for the final consumer, because no OTA residues were found in breast and thigh meat. Even though no clinical signs were noticed in the birds fed the OTA‐contaminated diet, moderate histological lesions were observed in the liver, spleen and bursa of Fabricius.